Polyglots in the Digital Age: Strategies and Hurdles in Learning Foreign Languages - Arif, Muhammad; Munirah, Munirah (Al-Lisan: Jurnal Bahasa, 2022)
This research aims to uncover how polyglots learn foreign languages, identifying both supporting and hindering factors in this learning process. The research method employed is a qualitative approach. The findings reveal that the model polyglots use to learn foreign languages involves studying one book in several languages. This method is the most effective and easiest way to enhance reading skills in various languages. Additionally, polyglots use several other strategies: they are unafraid to try, do not always rely on formal education, are persistent, seek productive habits, listen a lot, believe it is never too late to learn, seek communities or partners, find interconnections between languages, and adapt to their environment. Supporting factors for polyglots in learning foreign languages include having the talent for language acquisition, being motivated, and having the opportunity to learn. In contrast, hindering factors include an unsupportive environment, restrictive grammar, laziness, limited vocabulary, lack of focus, lack of commitment, and absence of clear goals in language learning.